Molecular Level Characterization of the Structure and Interactions in Peptide‐Functionalized Metal–Organic Frameworks. Issue 46 (11th October 2016) - Todorova, Tanya K.; Rozanska, Xavier; Gervais, Christel; Legrand, Alexandre; Ho, Linh N.; Berruyer, Pierrick; Lesage, Anne; Emsley, Lyndon; Farrusseng, David; Canivet, Jérôme; Mellot‐Draznieks, Caroline
Abstract: We use density functional theory, newly parameterized molecular dynamics simulations, and last generation 15 N dynamic nuclear polarization surface enhanced solid‐state NMR spectroscopy (DNP SENS) to understand graft–host interactions and effects imposed by the metal–organic framework (MOF) host on peptide conformations in a peptide‐functionalized MOF. Focusing on two grafts typified by MIL‐68‐proline (‐Pro ) and MIL‐68‐glycine‐proline (‐Gly‐Pro ), we identified the most likely peptide conformations adopted in the functionalized hybrid frameworks. We found that hydrogen bond interactions between the graft and the surface hydroxyl groups of the MOF are essential in determining the peptides conformation(s). DNP SENS methodology shows unprecedented signal enhancements when applied to these peptide‐functionalized MOFs. The calculated chemical shifts of selected MIL‐68‐NH‐Pro and MIL‐68‐NH‐Gly‐Pro conformations are in a good agreement with the experimentally obtained 15 N NMR signals. The study shows that the conformations of peptides when grafted in a MOF host are unlikely to be freely distributed, and conformational selection is directed by strong host–guest interactions. Abstract : Kept in its place : The first in‐depth study of metal–organic frameworks functionalized with peptides is reported whereby the key interactions at play and the conformations of the organic peptide grafts are unveiled through DFT calculations, molecular dynamics and last‐generation 15 N dynamic nuclear polarization surface enhanced solid‐state NMR spectroscopy. The results show that hydrogen bond interactions between the graft and the surface hydroxyl groups of the MOF are essential in determining the peptide conformations (see figure).